Modern approaches to diagnostics of hyperandrogenism distributed forms in reproductive aged women - О. А. Бурка; Т. М. Тутченко (Publishing House TRILIST, 2019)
Hyperandrogenism (HA) is characterized by elevated levels of circulating androgens and/or the presence of clinical manifestations their biological effects. HA incidence in the female population is around 8%. Causes of HA vary widely and its pathogenesis is not always completely clear. HA in women has a negative effect on fertility and metabolism. HA origins are divided into true adrenal or ovarian; peripheral/receptor; iatrogenic; transport and secondary. HA accompanies a fairly wide range of diseases and conditions. Most diseases are accompanied by mixed forms of HA, when there is a primary source and additional or secondary. The contribution of various HA sources in mixed forms may vary over time and depending on the exogenous or endogenous factors impact. Often an important HA component is free testosterone form predominance due to the reduced synthesis of sex hormone-binding globulin. All this dictates the need for a differentiated approach to the laboratory HA diagnosis for various diseases, especially fertility disorders. Such wide spread hyperandrogenic condition as PCOS not only affect female fertility but are also associated with increased life-long metabolic risks. Today it is recommended to use the following PCOS criteria: a combination of at least two of the three criteria: oligo/anovulation; polycystic ovarian morphotype; clinical or biochemical HA. Laboratory diagnosis of PCOS includes: tests to exclude other causes of HA and oligo/anovulation (differential diagnosis of PCOS), tests to confirm the diagnosis of PCOS according to criteria (biochemical HA evaluation), additional tests to diagnose PCOS, especially of normoandrogenic phenotypes forms; tests to diagnose the metabolic complications of PCOS.